2009
DOI: 10.1002/cm.20391
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical dynamics of single cells during early apoptosis

Abstract: Dynamic mechanical properties of cells are becoming recognized as indicators and regulators of physiological processes such as differentiation, malignant phenotypes and mitosis. A key process in development and homeostasis is apoptosis and whilst the molecular control over this pathway is well studied, little is known about the mechanical consequences of cell death. Here, we study the caspase-dependent mechanical kinetics of single cells during early apoptosis initiated with the general protein-kinase inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 58 publications
10
102
0
Order By: Relevance
“…Cuerrier et al [18] investigated the mechanical properties of human umbilical vein endothelial cells before and after drug treatment. Pelling et al [19] investigated the mechanical properties of human neonatal foreskin fibroblasts during early apoptosis by combining confocal microscopy and AFM. These studies were performed with conventional nanoscale AFM probe tips that are relatively sharp, and thus may cause damage to delicate cells.…”
mentioning
confidence: 99%
“…Cuerrier et al [18] investigated the mechanical properties of human umbilical vein endothelial cells before and after drug treatment. Pelling et al [19] investigated the mechanical properties of human neonatal foreskin fibroblasts during early apoptosis by combining confocal microscopy and AFM. These studies were performed with conventional nanoscale AFM probe tips that are relatively sharp, and thus may cause damage to delicate cells.…”
mentioning
confidence: 99%
“…Vinculin was labeled using 0.5% monoclonal anti-vinculin primary antibody produced in mouse (Sigma) and 0.5% rabbit anti-mouse IgG secondary antibody conjugated to AlexaFluor 546 fluorophore. DNA was labeled with 0.5% DAPI (Invitrogen) [21].…”
Section: Immunofluorescencementioning
confidence: 99%
“…The AFM was invented in 1986 as a scanning probe microscope (SPM) for the purposes of imaging [16] and has since been applied to biology for both imaging and measuring the mechanical properties of living cells [17][18][19][20][21]. Further insight into the mechanics of the CSK may be studied by the integration of AFM with optical imaging systems such as the ISRN Cell Biology 3 fluorescence microscope [19,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, fundamental biological processes such as apoptosis (cell death), mitosis, cancer metastasis, and stem cell fate are known to be modulated and even controlled by such mechanical cues [1,5,8,[10][11][12]18]. Wang and Pelling [22] showed that the nanomechanical breakdown of cells within a monolayer is governed by the depolymerization of F-actin within the cells, while the extracellular matrix (ECM) maintains the integrity of the sheet.…”
mentioning
confidence: 99%